Decreased expression of miR-939 contributes to chemoresistance and metastasis of gastric cancer via dysregulation of SLC34A2 and Raf/MEK/ERK pathway. Issue 1 (December 2017) - Zhang, Jia-Xing; Xu, Yi; Gao, Ying; Chen, Cui; Zheng, Zhou-San; Yun, Miao; Weng, Hui-Wen; Xie, Dan; Ye, Sheng
Abstract Background The development of chemoresistance and metastasis are the leading causes of death for gastric cancer (GC) patients, however, the molecular mechanisms involved remain unclear. Dysregulation of miRNAs is associated with a variety of disease, including GC. Recently, microarray profiling analysis revealed that miR-939 was dysregulated in human GC samples, but the role of miR-939 in GC has not been intensively investigated. Methods In the present study, we firstly examined the expression pattern of miR-939 in two independent cohorts of clinical GC samples: one cohort of 112 GC patients with stage I-III disease who underwent surgery followed by adjuvant chemotherapy; and another cohort of 110 GC patients with stage IV disease who received palliative chemotherapy. A series of in vivo and in vitro assays were then performed to investigate the function of miR-939 in GC. Results We detected that reduced expression of miR-939 was associated with chemoresistance and increased risk of tumor recurrence in GC patients. Further function study demonstrated that overexpression of miR-939 suppressed GC cell growth, and enhanced 5-fluorouracil-induced chemosensitivity by compromising cellular growth and inducing apoptosis in vitro and in vivo. Moreover, miR-939 repressed the migration and invasion of GC cells in vitro, and diminished the occurrence of lung metastasis in vivo. We further identified solute carrier family 34 member 2 (SLC34A2) was a novel target of miR-939. Mechanistically, we elucidated that miR-939 exerted its function mainly through inhibiting SLC34A2/Raf/MEK/ERK pathway, which is activated in GC. Multivariate analysis identified miR-939, SLC34A2, and their combination as independent indicators for poor prognosis and tumor recurrence in GC patients. Conclusion Our data indicate that miR-939 acts as a tumor suppressor miRNA in GC, and miR-939/SLC34A2 axis represents a novel therapeutic strategy for future GC treatment.